2022
DOI: 10.3390/ijerph19020942
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers’ Experiences and Coping Strategies in Managing Stroke Patients during the COVID-19 Pandemic: A Qualitative Exploration Study

Abstract: Background: Stroke is a chronic disease that requires stroke survivors to be supported long-term by their families. This is especially because of the inaccessibility to post-stroke rehabilitation outside hospitals. The Corona Virus Disease 2019 (COVID-19) crisis and the pandemic restrictions in Malaysia are expected to exponentially increase the demand from family caregivers in supporting stroke survivors. Thus, this study aims to explore the burden, experience, and coping mechanism of the family caregivers su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
6
0
4
Order By: Relevance
“…One of the most critical issues revealed by this study is what the participants reported about their feeling of burden on their family and their sense of burden caused as a result of their total or partial dependence on their families to help in accomplishing daily tasks, in addition to increasing the nancial burden on them. This is consistent with the results of previous studies where participants reported similar concerns [28,29].…”
Section: Discussionsupporting
confidence: 94%
“…One of the most critical issues revealed by this study is what the participants reported about their feeling of burden on their family and their sense of burden caused as a result of their total or partial dependence on their families to help in accomplishing daily tasks, in addition to increasing the nancial burden on them. This is consistent with the results of previous studies where participants reported similar concerns [28,29].…”
Section: Discussionsupporting
confidence: 94%
“…Even worse, some caregivers may feel abandoned if there is a lack of supports -financial, emotional, and social support [14,42]. Lack of access to patient care services may also contribute to the burden, whether the caregiver is unable to bring the patient due to lack of time, money, or logistics, or the services that were required by the patients or the caregivers were not available [7,12,42]. If the caregiver's burden is not dealt with appropriately, it may progress to other issues such as poor quality of life, anxiety, and depression [4,6,8,33].…”
Section: Discussionmentioning
confidence: 99%
“…Individualised regimes tailored to the needs of patients and the caregivers were more preferable, but lack of resources may limit some care providers to only delivering "one-size-fits-all" interventions [14,45]. Care providers should be aware of the availability of other types of support services available for the patients and their caregivers, including social, financial and spiritual support, both from government and non-governmental organisations [5,7,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] However, very little importance and lack of awareness exist among stroke rehabilitation experts, and the stroke survivors and their families for effective cognitive rehabilitation, respectively. [ 10 ] Cognitive impairments are also so complex in its presentation, implying that not one single interventional approach and its impact on the outcomes are sufficient to enhance functional recovery. Therefore, post-stroke cognitive rehabilitation includes a wide variety of interventions, approaches, and outcome measures to enable functional independence among those affected.…”
Section: B Ackgroundmentioning
confidence: 99%